If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-7 + 2y) + -6 = 0 (-7 * -3 + 2y * -3) + -6 = 0 (21 + -6y) + -6 = 0 Reorder the terms: 21 + -6 + -6y = 0 Combine like terms: 21 + -6 = 15 15 + -6y = 0 Solving 15 + -6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -6y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -6y = 0 + -15 -6y = 0 + -15 Combine like terms: 0 + -15 = -15 -6y = -15 Divide each side by '-6'. y = 2.5 Simplifying y = 2.5
| -38x+7=159 | | (-9ln(x)-6)/(x^2)=0 | | 10=2x(8)+b | | 12s-s=22 | | -32x=-4 | | 3x=(x*x)-40 | | 18/6d-9=1/6 | | p=2k-2w | | 3X+5X-8=15-X | | Y^2+6Y=-20x-89 | | 9x+17(x+1)=17-4x | | X+7=-4x+2 | | -3n+4=n-3n | | 8.5w=-119 | | (2x-y+5z)(2x-y-5z)= | | 9x+(x+1)=17-4x | | 4w-6=11 | | 7y+5x=148 | | (x-6)/4 | | (k-2)x^2-5x+2=0 | | 5(-3-2m)+7m= | | -35x=35 | | 20=2x+1.5y | | 14.82+w=28.82 | | log(4x+3)+log(3)=log(11x+12) | | 2x+6y=168 | | 7/9x3 | | y=-1(-6)+6 | | -141=-6+5(1+7x) | | 2(x-1)-6=10-(1-x)+6 | | 12x^2-1=-8x | | 8x=6-12 |